التصكيك والتوريق وسندات المقارضة: دراسة مدلولاتها اللغوية والشرعية وطرق استخدامها في سوق رأس المال الإسلامي = Securitization, securitization and Muqaradah bonds: a study of their linguistic and Sharia implications and methods of using them in the Islamic capital market - Saleh, Abdulmajid Obaid Hasan; Adam Sa'ad, Auwal; Rohman, Ghifary Duyufur Rohman (IIUM Press, 2021)
The study of sharia terminologies is very important. It is part of a conceptual study that helps researchers distinguish between scientific terms, especially in Islamic finance. In Islamic Finance, several terms overlap with other sciences, such as in the subject of Sukuk studies, and what is close or similar in several concepts, such as taskik and tasnid, tawarruq tashim, and so on. Researchers use descriptive and analytic methods by extrapolating terms related to these Sukuk, studying them in terms of origin and areas of use in contemporary issues. The study examined the linguistic and legal source of terms related to Islamic instruments, and the study concluded: Taskik, Tawriq, and Tasnid is a term for one name that indicates one meaning, except that the Sukuk term has become a popular term among the public regarding Islamic investment by the principles and provisions of the Sharia. However, Islamic economic researchers are not commonly used the taskik and tasnid terms because of their relevancy with conventional investment. And Tawriq is the act of converting money to be invested into Sukuk for sale. And the terms Tawriq and Taskik have similarities in this sense, namely converting assets into securities and transferring them to the Tawriq Company, which issues bonds and offers them toinvestors.